PENGARUH MINUM JAHE MERAH TERHADAP RASA NYERI PERSALINAN KALA II PADA PRIMIGRAVIDA DI KLINIK MUTIARA MEDIKA RANGKASBITUNG - Husnida, Nintinjri; kuswandi, kadar; Rokayah, Yayah (Jurnal Medikes (Media Informasi Kesehatan), 2023)
produce levels of pain that often exceed the limits of physical endurance. During labor itself, there are other variables that make each woman’s perception of pain unique, namely the frequency of contractions, the size and position of the baby, the length of labor, freedom of movement, the degree of fatigue and anxiety, feeling alone versus being supported and the amount of self-confidence and readiness. This study aims to determine the effect of red ginger drink on labor pain in the second stage of primigravida at Mutiara Medika Clinic, Rangkasbitung in 2022. The design used in this research is quasi-experimental. Research variables 25 grams of red ginger, 50 grams of red ginger, pain scale II. Data were collected through observation sheets from the results of the intervention of giving red ginger to the second stage of labor. The sample used was 29 primigravida mothers for each control and intervention group with a total of 87 people. Data analysis with the results of the bivariate test analysis used the Wilcoxon non-parametric test to test the difference in mean pain before and after the intervention in each group of women giving birth, and the Kruskal-Wallis test to test the difference in mean delta pain between groups of women giving birth. From the research that has been done, it was found that the highest mean reduction in pain and a statistically significant decrease occurred in maternity mothers who were given milk plus 50 grams of ginger. The difference in pain reduction between groups was statistically significant (p=0.000). The doses used were 25 grams of red ginger and 50 grams after testing and statistical calculations, the 50 gram dose was the most effective proven to reduce pain scale in maternity mothers. Midwives as health workers who directly deal with mothers in labor and their families, must be able to provide education and apply the use of red ginger powder to reduce pain in the second stage of labor for mothers in labor and their families.